The meteor hunt : the first English translation of Verne's original manuscript = La chasse au météore - Verne, Jules, 1828-1905 (Bison frontiers of imagination., 2006)
"The Meteor Hunt marks the first English translation from Jules Verne's own text of his satirical and visionary novel. While other, questionable versions of the novel have appeared - mainly, a significantly altered text by Verne's son Michel and translations of it - this edition showcases the original work as Verne wrote it." "The Meteor Hunt is the story of a meteor of pure gold careening toward the earth and generating competitive greed among amateur astronomers and chaos among nations obsessed with the trajectory of the great golden object. Set primarily in the United States and offering a humorous critique of the American way of life, The Meteor Hunt is finally given due critical treatment in the translators' foreword, detailed annotations, and afterword, which clearly establish the historical, political, scientific, and literary context and importance of this long-obscured, genre-blending masterpiece in its true form."--Jacket.